PELATIHAN KEWIRAUSAHAAN MENGGUNAKAN METODE DESIGN THINKING BAGI SISWA DI SMA IT INSAN MULIA BOARDING SCHOOL - Sinatria, Naufal; Fauzan Fuadi; Raidah Hanifah; Muhammad Lathief Syaifussalam; Meilia Wigati (Dharma: Jurnal Pengabdian Masyarakat, 2025)
Entrepreneurship is a strategic step to create job opportunities and enhance economic independence. In an era of globalization and technological advancement, entrepreneurial skills are key to preparing the younger generation to face intense job market competition. Design Thinking, a method based on user input, technology, and solutions, is used to develop businesses. The community service activity at SMA IT Insan Mulia Boarding School involved 21 eleventh-grade students through lectures, discussions, and practical simulations. Evaluations showed that this training successfully provided a positive impact, especially for Generation Z. Based on a 1-5 scale, most participants rated the program 4 (Good) to 5 (Very Good), indicating that the training met their expectations and needs.